1981
DOI: 10.1002/1097-0142(19810201)47:3<615::aid-cncr2820470332>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma in dominant type epidermolysis bullosa dystrophica

Abstract: The unusual genetic disorder epidermolysis bullosa dystrophica has been reported in several patients in whom the chronic cutaneous scars led to the development of cutaneous squamous cell carcinoma. However , only one of these previously reported cases involved the autosomal dominant form of the disease; the remainder occurred in its recessive counterpart. We report the second and third patients with squa-mous cell carcinoma associated with the dominant form of epidermolysis bullosa dystrophica. In addition , w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 21 publications
0
30
0
1
Order By: Relevance
“…Reed et al further provided evidence to suggest that these tumors frequently resulted in death from metastases (having occurred in over two thirds of all previously reported patients). Others have since published case reports or small case series confirming this association and suggesting that SCCs also arise in DDEB 16,17 and JEB. [18][19][20][21][22] There has also been a report of a child with RDEB in whom a superficial spreading MM arose.…”
Section: Discussionmentioning
confidence: 79%
“…Reed et al further provided evidence to suggest that these tumors frequently resulted in death from metastases (having occurred in over two thirds of all previously reported patients). Others have since published case reports or small case series confirming this association and suggesting that SCCs also arise in DDEB 16,17 and JEB. [18][19][20][21][22] There has also been a report of a child with RDEB in whom a superficial spreading MM arose.…”
Section: Discussionmentioning
confidence: 79%
“…Due to its toxicity, systemic chemotherapy is generally avoided for EB patients, and there are only four reports of its use in EB associated cSCC [21, 2729]. Lentz et al , showed good tolerance for two patients with RDEB; one of them was treated with cisplatin alone, the other one with a combination 5-FU-cisplatin, with no significant toxicity to the skin or oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…When using radiotherapy, consideration needs to be given to severe desquamation that can follow larger total radiation doses. Conventional chemotherapy has been used in cases of advanced EB SCCs (32)(33)(34)(35). Agents have included cisplatin, carboplatin, paclitaxel, fluorouracil, doxorubicin and methotrexate.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%